Berkley's critique of Locke;s distinction between Primary and Secondary qualities - An analytical study based on A Treatise concerning the principal of Human Knowledge. - Poologanathan, P. (South Estern University of Sri Lanka, 2015)
This research is a study of how Barkley rejects the distinction of Primary and Secondary qualities put forwarded by John Locke, regarding Human Knowledge in his book “A Treatise concerning the principle of human knowledge”. Empiricist John Lock said that the human knowledge is obtained through two ways which are perception and reflection. And what the mind sees immediately from this internal impressions he called “ideas”. Locke differentiated them into simple ideas and complex ideas. External matters have inherent powers to create these ideas within us. Locke called these powers “Qualities”. These qualities were differentiated into primary and secondary qualities. Locke had revealed in his book, “An Essay concerning Human understanding” that Primary qualities are concerned with materials and secondary qualities are not concerned materials, it is different human to human. Although Locke differentiated between these two qualities, he could not clarify the relationship between them. Hence, so as to rectify this short comings, Berkley reject Lock’s quality differentiation in his book and try to reach a solution by explaining that the primary and secondary qualities co-exist indivisibly, and all these remain relative to our mind and nothing else. For explain this study Analytical method and critical method are utilized and data for the study were obtained from literature, magazines, and internet
Keywords: Primary Qualities; Secondary Qualities; Ideas; Simple ideas; Complex ideas; Sensations